Penerapan Knowledge Managemen System Sales And Customer Care Pada PT. Telkomsel Regional Sumbagsel - Putri Silpiara; Ken Ditha Tania (Jurnal Sistem Informasi, 2015)
Abstract PT. Telkomsel Regional Sumbagsel have a big desire to apply knowledge management system, Therefore documenting knowledge and The utilization need to managed well in the context of increasing performance. Applicabilitty of knowledge management in PT. Telkomsel Regional Sumbagselw here is every employe can save, documenting, and share knowledge to each other have a very good rated and give a positive effect for quality of employees. It make the employee can save and documenting and share knowledge to each other. So, the employees can access, even, to learn and discuss to other employees based on the knowledge that in the post. Then , when they needed to the knowledge , it will easy to find in the database with searching fiture in knowledge management system of web based on PT. Telkomsel Regional Sumbagsel. As for this system made using SECI. The methodology used in this study refers to the KM methodology who developed by Amrit Tiwana (1999), later , the system based web will use programming language PHP. Keywords : Knowledge Management Abstrak PT. Telkomsel Regional Sumbagsel memiliki keinginan besar untuk menerapkan Knowledge management system, oleh karena itu pendokumentasian pengetahuan dan pemanfaatannya perlu dikelola dengan baik dalam konteks peningkatan kinerja. Dapat diterapkannya knowledge management di PT Telkomsel Regional SumbagselÂ  ini dinilai sangat baik dan dapat berefek positif bagi kualitas pegawai. Dimana setiap pegawai dapat menyimpan dan mendokumentasikan serta sharing pengetahuan yang dimiliki, sehingga pegawai lain dapat mengakses, bahkan mempelajari dan berdiskusi dengan pegawai lain berdasarkan pengetahuan yang di-posting, kemudian saat dibutuhkan suatu pengetahuan tersebut, sangat mudah ditemukan di dalam database dengan fitur searching dalam knowledge management system berbasis web pada PT Telkomsel Regional Sumbagsel. Metodologi yang digunakan pada penelitian ini merujuk pada metodologi KM yang di kembangkan oleh Amrit Tiwana (1999), dan sistem ini nantinya berbasis web dengan menggunakan bahasa pemrograman PHP. Kata kunci: Mengelola Pengetahuan